Anarchic solidarity : autonomy, equality, and fellowship in South east Asia - Gibson, Thomas, 1956-; Sillander, Kenneth (New Haven, Conn. : Yale University Southeast Asia Studies)
"This volume analyzes a group of Southeast Asian societies that have in common a mode of sociality that maximizes personal autonomy, politi cal egalitarianism, and inclusive forms of social solidarity. Their mem bers make their livings as nomadic hunter-gatherers, shifting cultivato rs, sea nomads, and peasants embedded in market economies. While politi cal anarchy and radical equality appear in many societies as utopian id eals, these societies provide examples of actually existing, viable for ms of "anarchy." This book documents the mechanisms that enable these s ocieties to maintain their life-ways and suggests some moral and politi cal lessons that those who appreciate them might apply to their own soc ieties"--Back cover.
Includes bibliographical references and index.
Keywords: Anarchy -- Social aspects -- Southeast Asia; Solidarity; Autonomy -- Social aspects -- Southeast Asia; Equality -- Social aspects -- Southeast Asia; Fellowship -- Social aspects -- Southeast Asia; Social structure; Southeast Asia -- Social life and customs; Southeast Asia -- Social conditions; Southeast Asia -- Politics and government